Characteristic Patterns of Traditional Settlements in the Keraton Malay Area: Case studies in Pontianak, Kuala Terengganu, and Kampung Glam - Gunawan, Ivan; Mustikawati, Mustikawati (International Journal of Environment, Architecture, and Societies, 2025)
Traditional settlements or villages emerged during the empire. Kampongs tend to be located on the banks of rivers and are located near palaces or imperial palaces. The Kadriah Palace, Istana Maziah and Glung Kampung Palace are the Malay sultanate palaces which develop along with the surrounding traditional settlements (kampongs). This study aims to explore the traditional settlement patterns of the Malay community across three countries; Indonesia, Malaysia, Singapore, to see similarities and differences in settlement patterns. This research is a qualitative-descriptive research with comparative analysis. Differences and similarities will define the existence level of identity of the types of settlement patterns around the palace. Settlement Patterns in the three locations have the same pattern, that is, an elongated pattern or a line or linear pattern with the process of splitting from the river bank to the land. Cultural boundary of traditional settlements is in all three locations where houses are grouped in one place based on ethnicity.